Jomtien, EFA goals and lessons from the ground : the challenge for the Dakar Conference - Chowdhury, A Mushtaque R.; Choudhury, Rasheda K.; Nath, Samir Ranjan (BRAC Research and Evaluation Division (RED), 2020)
It is now almost ten years since the last World Conference on Education for All (WCEFA), held in Jomtien, Thailand, had called for ensuring basic education to at least 80% of the children. This paper, with latest field level data, argues that the dream of 'education for all' (EFA) has still remains a distant dream for an impoverished country like Bangladesh. There are, of course, hopes. The enrollment has increased (particularly for girls), the completion rate has risen, and the poor and less educated parents are sending their daughters in larger numbers to school than before. But the progress in terms of net enrollment has been rather slow and the children are not learning much in school. With a net enrollment of 73%, 70% completing the primary cycle, and 57% of those completing grade 5 achieving' basic education', not even 30% are receiving any meaningful education. The analysis shows that the rate of progress in terms of achieving a minimum level of basic education has been slow-- less than one percentage point per year. The Bangladesh picture has great implications for the countries meeting for the next decennial WCEFA in Dakar, Senegal. The challenge for the world is how to achieve EFA at the shortest possible time. In this, investment in education in general and its distribution, pluralism in delivery system, appropriate curriculum, positive discrimination in favor of disadvantaged groups, and a supportive supervision and monitoring system will be important ingredients.